Implementing public involvement throughout the research process—Experience and learning from the GPs in EDs study. (27th July 2022) - Evans, Bridie Angela; Carson‐Stevens, Andrew; Cooper, Alison; Davies, Freya; Edwards, Michelle; Harrington, Barbara; Hepburn, Julie; Hughes, Tom; Price, Delyth; Siriwardena, Niroshan A.; Snooks, Helen; Edwards, Adrian
Abstract: Background: Public involvement in health services research is encouraged. Descriptions of public involvement across the whole research cycle of a major study are uncommon and its effects on research conduct are poorly understood. Aim: This study aimed to describe how we implemented public involvement, reflect on process and effects in a large‐scale multi‐site research study and present learning for future involvement practice. Method: We recorded public involvement roles and activities throughout the study and compared these to our original public involvement plan included in our project proposal. We held a group interview with study co‐applicants to explore their experiences, transcribed the recorded discussion and conducted thematic analysis. We synthesized the findings to develop recommendations for future practice. Results: Public contributors' activities went beyond strategic study planning and management to include active involvement in data collection, analysis and dissemination. They attended management, scrutiny, planning and task meetings. They also facilitated public involvement through annual planning and review sessions, conducted a Public Involvement audit and coordinated public and patient input to stakeholder discussions at key study stages. Group interview respondents said that involvement exceeded their expectations. They identified effects such as changes to patient recruitment, terminology clarification and extra dissemination activities. They identified factors enabling effective involvement including team and leader commitment, named support contact, building relationships and demonstrating equality and public contributors being confident to challenge and flexible to meet researchers' timescales and work patterns. There were challenges matching resources to roles and questions about the risk of over‐professionalizing public contributors. Conclusion: We extended our planned approach to public involvement and identified benefits to the research process that were both specific and general. We identified good practice to support effective public involvement in health services research that study teams should consider in planning and undertaking research. Public Contribution: This paper was co‐conceived, co‐planned and co‐authored by public contributors to contribute research evidence, based on their experiences of active involvement in the design, implementation and dissemination of a major health services research study.